2015
DOI: 10.1002/dvdy.24293
|View full text |Cite
|
Sign up to set email alerts
|

Expression of SPARC and the osteopontin‐like protein during skeletal development in the cichlid fish Oreochromis mossambicus

Abstract: Background: Bones are mainly composed of calcium hydroxyapatite and a proteinous matrix. In this study, we focus on the bone matrix proteins, the fish osteopontin orthologous protein (osteopontin-like protein; OP-L) and SPARC, because the current knowledge regarding their expression is fragmentary or contradictory. Results: We first provide a comprehensive and detailed description of skeletal development in the cichlid fish Oreochromis mossambicus. Following this, we analyzed the expression pattern of OP-L and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 69 publications
(96 reference statements)
2
6
0
Order By: Relevance
“…The PCR reaction was performed on cDNA and the products of the correct size were cloned in the pGEM®‐T Easy Vector (Promega, Madison, USA), sequenced on both strands and checked by blast against the NCBI database. The cloning procedure of OMP‐1, otolin‐1 and SPARC was previously described in Weigele et al, (). Successful PCR primers for PCLP were PCR 5′‐GGGAT(AC)TCGGTG CGCTC‐3′; 5′‐TT(GC)TGCATCAGGCT(AGCT)ACCTG −3′.…”
Section: Methodsmentioning
confidence: 99%
“…The PCR reaction was performed on cDNA and the products of the correct size were cloned in the pGEM®‐T Easy Vector (Promega, Madison, USA), sequenced on both strands and checked by blast against the NCBI database. The cloning procedure of OMP‐1, otolin‐1 and SPARC was previously described in Weigele et al, (). Successful PCR primers for PCLP were PCR 5′‐GGGAT(AC)TCGGTG CGCTC‐3′; 5′‐TT(GC)TGCATCAGGCT(AGCT)ACCTG −3′.…”
Section: Methodsmentioning
confidence: 99%
“…However, not much is known about these cells or their function. Avaron et al (2006) and Weigele et al (2015) indicated that osteoblast-like cells are OP-L positive and might therefore be involved in the deposition of bone matrix. However, these cells have few other characteristics of typical osteoblasts .…”
Section: Zebrafish Possess Cellular and Acellular Bonesmentioning
confidence: 99%
“…Available expression analyses did not report any cartilaginous expression for SCPP genes in teleosts ( Kawasaki et al, 2005 ; Kawasaki, 2009 ; Weigele et al, 2015 ). Rather, the expression of the SPARC gene has been associated to cartilage development in zebrafish, gilthead seabream and the cichlid mouth breeder ( Estevao et al, 2005 ; Redruello et al, 2005 ; Rotllant et al, 2008 ; Estevao et al, 2011 ; Weigele et al, 2015 ), albeit not in medaka, at least at the examined stages ( Renn et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Available expression analyses did not report any cartilaginous expression for SCPP genes in teleosts ( Kawasaki et al, 2005 ; Kawasaki, 2009 ; Weigele et al, 2015 ). Rather, the expression of the SPARC gene has been associated to cartilage development in zebrafish, gilthead seabream and the cichlid mouth breeder ( Estevao et al, 2005 ; Redruello et al, 2005 ; Rotllant et al, 2008 ; Estevao et al, 2011 ; Weigele et al, 2015 ), albeit not in medaka, at least at the examined stages ( Renn et al, 2006 ). Hence the reported cartilaginous expression patterns in teleosts ( SPARC positive and SCPP negative) are opposite to the tetrapod situation ( SPARC negative and SCPP positive), which might be related to drastic difference in the mode of endochondral ossification between these two groups ( Cervantes-Diaz et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%